Study of the availability of home modifications in paraplegics - Chavhan, Dinesh G.; Mehta, Amita A.; Iyer, Sarasawti (International Journal Of Community Medicine And Public Health, 2024)
Background: Paraplegia is loss of motor strength, sensations and bowel bladder function below the level of injury due to spinal cord damage. Spinal cord injury is medically managed along with rehabilitation which includes muscle strengthening, and mobility in a wheelchair with proper training and home modification. The paraplegic population is the most demoted section of our society and is confronted with barriers to accessibility, health facilities, educational opportunities, and skill development. Accessibility is very important for the paraplegic population and lack of accessibility may affect their abilities in self-care and employment so our objective was to find out modifications done in the house of paraplegics, compartmentalize and standardize various modifications done. Methods: The study setting and design was done at tertiary care centre, community setting and observational study. The sample size was 40. Inclusion was of both genders, sub-acute to chronic phase spinal cord injury and wheelchair users was taken. Exclusion was quadriplegics and bedridden patient’s spinal cord injury individual. Results: The statistical analysis was done by using SPSS V 26 software. The mean and standard deviation were calculated. In this study, the mean average modification shows in the ascending order of the entrance and exits (69.5%), followed by the hall (64.30%), bedroom (60%) bathroom (60%) and the kitchen (37.5%). Conclusions: The study concluded that most of the spinal cord injury individuals modify their houses. Entrance, exits and followed by the hall were most modified and the kitchen was the least modified compartment in the house.